2014
DOI: 10.1016/j.celrep.2014.06.017
|View full text |Cite
|
Sign up to set email alerts
|

Yorkie Promotes Transcription by Recruiting a Histone Methyltransferase Complex

Abstract: SUMMARY Hippo signaling limits organ growth by inhibiting the transcriptional coactivator Yorkie. Despite the key role of Yorkie in both normal and oncogenic growth, the mechanism by which it activates transcription has not been defined. We report that Yorkie binding to chromatin correlates with histone H3K4 methylation, and is sufficient to locally increase it. We show that Yorkie can recruit a histone methyltransferase complex, through binding between WW domains of Yorkie and PPxY sequence motifs of NcoA6, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
66
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(70 citation statements)
references
References 54 publications
3
66
1
Order By: Relevance
“…Using DDIT4 and Trail as examples, we showed that the repressor activity of YAP/TAZ contributes to their oncogenic functions ( Figure 6). Recent studies have shown that YAP-TEAD recruits the NcoA6 H3K4 methyltransferase complex and SWI/SNF chromatin-remodeling complex for target gene activation (Oh et al, 2013(Oh et al, , 2014Qing et al, 2014;Skibinski et al, 2014). Together with these studies, our results significantly improve understanding of the transcriptional control exerted by YAP/TAZ (Figure 7).…”
Section: Discussionsupporting
confidence: 58%
“…Using DDIT4 and Trail as examples, we showed that the repressor activity of YAP/TAZ contributes to their oncogenic functions ( Figure 6). Recent studies have shown that YAP-TEAD recruits the NcoA6 H3K4 methyltransferase complex and SWI/SNF chromatin-remodeling complex for target gene activation (Oh et al, 2013(Oh et al, , 2014Qing et al, 2014;Skibinski et al, 2014). Together with these studies, our results significantly improve understanding of the transcriptional control exerted by YAP/TAZ (Figure 7).…”
Section: Discussionsupporting
confidence: 58%
“…However, widespread loss of trr was found to result in reduced cell proliferation and tissue growth, possibly related to aberrant regulation of the highly conserved Notch signaling pathway. Two recent studies determined that the COMPASS-like complex subunits trr and NcoA6 are required for the activation of Hippo pathway target genes, another important signaling pathway in cell growth and apoptosis (111,112). Tissue-specific Cmi depletion using RNAi or overexpression of the wild-type Cmi protein produced strong patterning-defect phenotypes consistent with altered Tgf-b/ Dpp signaling, and Cmi protein localization experiments suggested possible direct regulation of dpp transcription enhancer regions (20).…”
Section: Pathway Analysis Of Mll3/kmt2c and Mll2/ Kmt2d Deficiencymentioning
confidence: 95%
“…NCOA6 is a common coactivator (107) and has been demonstrated to be essential for embryo development and survival through knock-out studies in mice (108e110). The Drosophila NcoA6 gene has also been shown to be important for viability and proper tissue development through interaction with the Yorkie/YAP transcriptional activator involved in the Hippo signaling pathway (111,112). NCOA6 has been shown to associate with a large variety of nuclear hormone receptors, including prostanoid, retinoid, vitamin D3, thyroid hormone, and steroid receptors in humans, enhancing the activating ability of these transcription factors.…”
Section: Components Of the Human Kmt2c/kmt2d Compass-like Complexesmentioning
confidence: 97%
“…Many genes are transcriptionally activated by TEAD complexed with YAP and/or TAZ (Zhu et al 2015). Mechanistically, YAP and TAZ stimulate TEAD transcriptional activity by recuriting components of the SWI/SNF chromatin remodeling complex or NCOA6 histone methyltransferase complex (Oh et al 2013(Oh et al , 2014Qing et al 2014;Skibinski et al 2014). Interestingly, the YAP/TAZ-TEAD complex can also operate as transcriptional corepressors by recruiting the NuRD histone deacetylate complex for additional target genes, such as DDIT4 and Trail regulation.…”
Section: The Yap/taz Transcriptional Programs and Their Functional Oumentioning
confidence: 99%